Meningkatkan Efisiensi Layanan Fotokopi Melalui Metode Antrian Yang Tepat - Audya, Anggi; Putri, Pujawati Kurnia; Hasibuan, Vivi Indriani; Srikandy, Yuyun Lili; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
Efficient photocopying services are essential to meet customer needs in this fast-paced era. This article discusses the importance of implementing the right queuing method to improve the efficiency of photocopying services. With the increasing demand for photocopying services, long queues are often a problem that disrupts the customer experience. Through an analysis of various queuing methods, such as digital queuing systems, virtual queues, and self-service kiosks, this article identifies the advantages and disadvantages of each method. It also presents case studies of several copy shops that have successfully implemented modern queuing methods, showing significant improvements in waiting time and customer satisfaction. The results show that implementing the right queuing method not only reduces waiting time but also increases employee productivity and customer loyalty. This article is expected to provide insights for copy shop owners in optimizing their services through effective queue management.